Applications of Soft Sets in K-Algebras. (3rd March 2013) - Alshehri, N. O.; Akram, M.; Al-ghamdi, R. S.
Abstract : In 1999, Molodtsov introduced the concept of soft set theory as a general mathematical tool for dealing with uncertainty and vagueness. In this paper, we apply the concept of soft sets to K -algebras and investigate some properties of Abelian soft K -algebras. We also introduce the concept of soft intersection K -algebras and investigate some of their properties.